Alleviation effects of grape seed proanthocyanidin extract on inflammation and oxidative stress in a d-galactose-induced aging mouse model by modulating the gut microbiota. Issue 3 (19th January 2022) - Sheng, Kangliang; Yang, Jian; Xu, Yifan; Kong, Xiaowei; Wang, Jingmin; Wang, Yongzhong
Abstract : Grape seed proanthocyanidin extract delayed the d -galactose-induced aging process in mice through the gut microbiota–liver axis and microbiota–brain axis. Abstract : Grape seed proanthocyanidin extract (GSPE) that prevents and alleviates the degenerative changes associated with aging has been receiving extensive attention. In our present work, the ageing model was induced by injection of 500 mg kg −1 d -galactose daily for a period of eight weeks. The d -galactose-induced ageing mice model was used for evaluating the effect of GSPE on oxidative stress, inflammation levels and gut microbiota composition. d -Galactose induced oxidative damage and inflammation with a significant increase in malondialdehyde contents, myeloperoxidase activities and the levels of TNF-α and IL-1β, as well as a reduction in the activities of glutathione peroxidase and reduced glutathione. Treatment with different doses of GSPE could significantly improve the antioxidant capacity and inflammation levels in the liver and brain, which is accompanied by increased Lachnospiraceae_NK4A136, Lactobacillus, Bifidobacterium, and Akkermansia, as well as decreased Helicobacter and Alistipes . In addition, the high-dose GSPE group exhibited greater potential to delay the ageing process than the low-dose group. Our results also showed that GSPE administration could downregulate the NLRP3 inflammasome signaling pathway for inhibiting inflammation levels in the brain tissue. This study provided a novel strategy to target the gut microbiota with regard to the effect of GSPE administration on alleviating aging-induced alterations via the gut microbiota–liver axis and gut microbiota–brain axis.